The Continuity of Muslim Worship during Pandemic to the Post-Pandemic - Jubba, Hasse; Fernando, Henky; Larasati, Yuniar Galuh (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
The rules and attitudes of Muslim worship during the Covid-19 pandemic are still continuously applied by the Masjid Gede Mataram Kotagede Yogyakarta in the post-pandemic period. Studies that have discussed this phenomenon focus on the adaptation and recovery process of religious activities, so they have not comprehensively discussed the rules and attitudes of post-pandemic Muslim worship. This study focuses on the question,